Fibrinogen: Risk Factor for Cardiovascular Disease - Kafle, Dilli Ram (Journal of Nobel Medical College, 2012)
Patients with diabetes mellitus have 2 to 4 times increased risk for cardiovascular disease than non-diabetic patients. However this excess risk is not fully explained by the traditional cardiovascular risk factors (Hypertension, Hypercholesterolaemia, Smoking and Obesity) which are also associated with diabetes. Fibrinogen has been identified as an independent risk factor for cardiovascular disease and it is associated with traditional cardiovascular risk factors. Studies done in the Caucasians have shown fibrinogen to be higher in diabetic than the non-diabetic patients. Elevated fibrinogen in diabetic patients may be responsible for the increased cardiovascular risk in those patients. Elevated fibrinogen is also associated with increased mortality in general population. DOI: http://dx.doi.org/10.3126/jonmc.v1i1.7281 Journal of Nobel Medical College Vol.1(1) 2011 1-8